Pola Alih Tutur dalam Naskah Drama First Love Karya Inggrida Wisnu S. - Sri Puji Astuti (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
The purpose of this research is to describe the pattern of turn-taking and how to get the turn-taking contained in the drama of First Love by Inggrida Wismu S. This research is a qualitative descriptive study. Methods of data collection in this research is an observation method means that observe to the play script drama of First Love by Inggrida Wisnu S. the source of data obtained by online media. The data obtained in this research was a fragment of taking. Then, the data was analyzed by using the pattern of turn-taking. The results showed that the pattern of turn taking based on the closest adjacency pair contained in the drama of First Love script was (1) the question was followed by the answer, (2) greeting was followed by salam, (3) the call was followed by the answer, (4) farewell expression was followed by message, (5) ) praise was followed by refusing, (7) complain was followed by questioning, answering, offering, and refusing, (8) accusing was followed by refusing and admitting (9) the petition was followed by agreement, petition, suspension, petition, granting. As for turn-taking in the First Love drama by Inggrida Wisnu S used how to acquire, steal, create, continue, and seize.